Nonfarm Activity and Rural Income Inequality : A Case Study of Two Provinces in China - Zhu, Nong; Luo, Xubei (World Bank, Washington, DC, 2012)
Nonfarm activity plays an increasingly important role in rural household income. Based on data from the Living Standards Measurement Study in the provinces of Hebei and Liaoning, the authors study the distribution of nonfarm income in rural China. First, they assume nonfarm income as an exogenous transfer to total income to decompose the Gini index. Second, they assume nonfarm income as a potential substitute for farm income to take household choices into account and simulate household income. The results show that nonfarm activity reduces rural income inequality by raising the income of poor households to a larger extent than that of rich households. Improving rural infrastructure and implementing universal basic education are critical to build up the capacity of households (in particular, poor households) to participate in nonfarm activity. Strengthening the links between farm activity and nonfarm activity is essential to optimize the contribution of nonfarm activity to pro-poor rural economic development.